Photophysical properties and theoretical photosensitization mechanism of non-peripherally dodecyloxy substituted metallophthalocyanines for photodynamic therapy. Issue 9 (2nd September 2021) - Murali krishnan, M.; Baskaran, S.; Arumugham, M. N.
Abstract: Non-peripherally tetradodecyloxy substituted copper (CuPc 3 ) and nickel (NiPc 4 ) phthalocyanines and the compounds were synthesized. The absorption spectra of synthesized Pcs were showed monomeric behavior evidenced by a narrow between 680 and 750 nm (Q band) for CuPc(3 ) and NiPc(4 ) in different solvents. The fluorescence behavior of the Pcs was studied in chloroform. The CuPc (3 ) showed outstanding stability in THF as solvent during photodegradation studies. The possible photodynamic therapy reaction mechanisms were studied through the calculation of ionization potentials and electron affinity in both vacuum and solvents using SCRF model.